Treatment of Unresectable Differentiated Thyroid Carcinoma With Upfront External Radiotherapy and Salvage Surgery: A STROBE-Compliant Retrospective Cohort Study - Carrillo, José F.; Flores, Jesús Manuel; Espinoza, Gilberto; Vázquez-Romo, Rafael; Ramírez-Ortega, Margarita C.; Carrillo, Liliana C.; Cortés-García, Beatriz Y.; Ochoa-Carrillo, Francisco J.; Oñate-Ocaña, Luis F. (Frontiers in Oncology, 2021)
Introduction. In patients with unresectable Differentiated thyroid cancer (DTC), the use of external beam radiation therapy (EBRT), leads mostly to palliation. Our aim is to define the role of upfront EBRT, followed or not by rescue surgery, on Progression-free survival (PFS) or Overall survival (OS) in patients with DTC. Methods. This is a cohort study of patients with initially unresectable DTC who received EBRT. Cohort A received EBRT followed by rescue surgery and cohort B, EBRT only. The Kaplan-Meier method and Cox model were employed for survival analysis. Results. Thirty-three patients were included; 69.6% females and 30.3% males. Mean age was 60.6 and mean tumor diameter was 10.4 cm; 17 and 16 patients were included in cohorts A and B, respectively. Belonging to cohort A (Hazard ratio [HR] 0.177, 95% CI 0.05-0.7) and use of intensity modulated radiotherapy (HR 0.177, 95% CI 0.03-1.08) were associated to better PFS, while high-risk histopathology (HR 6.6, 95% CI 0.9-50) and EBRT dose (HR 1.05, 95% CI 1.01-1.08) were independently associated with lower PFS. Patients from cohort A (HR 0.061, 95% CI 0.01-0.3) had improved OS, while high-risk histopathology (HR 5.7, 95% CI 1.1-28.6) and EBRT dose (HR 1.05, 95% CI 1.01-1.09) were independently associated to worse OS. Conclusion. EBRT, and when feasible, rescue surgery, should be an integral part of the therapeutic strategy in initially unresectable DTC.